(untitled) (Nigerian Journal of Physiological Sciences, 2019)
In this study, the changes in gonadal oxidative stress markers and reproductive function of BALB/c mice were investigated. Forty-eight (48) BALB/c mice acquired for this study were randomly divided into four groups of eight mice each. Each group was further sub-divided into male and female groups with equal number of mice. The groups were represented as thus: Group A: normal mice; Group B: mice infected with malaria parasite, Plasmodium berghei; Group C: malaria infected mice treated with Artemether/Lumefantrine; Group D: malaria infected mice treated with Vitamin E. The experimental mice were inoculated with the Plasmodium bergehi, and the malaria parasite were confirmed in the mice four days later before the commencement of the experiments. After the experimental procedures which lasted for fourteen (14) days, the mice were sacrificed, blood samples collected for serum testosterone, estrogen and progesterone assay; semen were collected for semen analysis; and testes and ovaries were harvested for histological analysis and oxidative stress marker determination. Result show that malaria parasite, Plasmodium berghei significantly (p<0.05) decreased the sperm count, percentage of sperm with progressive motility and percentage of sperm with normal morphology. The malaria parasite also decreased the serum concentrations of testosterone, estrogen and (p<0.05) progesterone. Plasmodium berghei, also caused significant (p<0.05) reductions in testicular and ovarian activities of superoxide dismutase, catalase and glutathione peroxidase while significantly (p<0.05) increasing the malonaldehyde level. The malaria parasite also caused marked histological distortions in the testes and ovaries of the mice. Treatment with Artemether/Lumefantrine and Vitamin E separately reversed the detrimental changes induced by the malaria parasite by increasing the semen quality and hormonal concentrations. Treatment with Artemether/Lumefantrine and Vitamin E also decreased the oxidative stress level of the gonads and improved the histological features of the testes and ovaries of the infected mice. Therefore, this study show that malaria infestation poses anti-fertility threat while treatment with Artemether/Lumefantrine and Vitamin E reverses the effect of the malaria parasite.